El discurso sobre la defensa de la Tau del médico valenciano Miguel Jerónimo Ledesma: un testimonio del griego renacentista - Santamaría Hernández, María Teresa; Herrera Santana, Juana (1999)
The Greek literary output was al so based on the imitatia from classical authors, during the Renaissance Humanism. A good example there of is the work written in Greek by the Valencian doctor Miguel Jerónimo Ledesma about the dispute between Tau and Sigma, inspired from the Iudicium Vocalium by Lucian. In this essay, both form and content parallelisms are studied between both texts, in order to reveal whether the literary composition technique used by the Valencian author can be similar to the one used in neolatin works.
Keywords: Lledesma, Miquel Jeroni, -- -1547; Discursos; Humanismo; Renacimiento; Lengua griega